Indirect effects of social support and hope on quality of life via emotional distress among stroke survivors: A three-wave structural equation model - Fong, Ted C. T.; Lo, Temmy L. T.; Ho, Rainbow T. H. (Frontiers in Psychiatry, 2022)
Objectives: Stroke survivors are prone to functional impairments and reduced quality of life (QoL). This study examined the mediating role of social support and hope in the relationships between functional impairment, emotional distress, and QoL. Methods: A total of 188 stroke survivors in Hong Kong completed assessments on functional impairment, social support, and hope at baseline, with follow-up measurements of emotional distress at 2 months and QoL at 8 months. Structural equation modeling with bootstrapping was used to analyze the direct and indirect effects of functional impairment on emotional distress and QoL via the mediating factors of social support and hope. Results: The partial cascading model provided an adequate fit to the data. Functional impairment had significant negative direct effects on hope and physical QoL and social support had significant positive direct effects on hope and physical QoL. Social support had a significant positive indirect effect on physical QoL via hope and perceived stress and on psychosocial QoL via hope and depression. Functional impairment and hope had a significant negative interaction effect on perceived stress. Conclusions: The findings support a mediating role for hope in the relationship between social support and QoL in stroke survivors. The protective effect of hope on perceived stress was stronger among patients with greater functional impairment.